Charting Community Voices: Mapping Methods in Health Equity Research and Community Engagement - Janessa M. Graves; Aspen Avery; Carmen Gonzalez; Megan Moore (International Journal of Qualitative Methods)
Rural Americans experience health disparities compared to those in urban areas, including higher incidence of disease, disability, and injury; higher mortality rates; and lower life expectancies. These disparities are driven, in part, by factors such as geographic isolation, transportation challenges, limited access to specialist healthcare providers, and socioeconomic disparities that impede equitable access to healthcare. These contextual factors are unique to each rural community, leading to challenges in developing appropriate and effective interventions to meet their unique health needs. There is no “one size fits all” approach: health interventions in the rural context must be tailored to each community’s unique characteristics, culture, and circumstances. We describe how three interdisciplinary mapping approaches (group concept mapping, communication asset mapping, and intervention mapping) can be used for engaging with rural communities in health equity research and, specifically, if used appropriately, can enhance community participation in the design of culturally tailored, accessible, and sustainable health services. Group concept mapping employs a participatory approach to gather and organize ideas from community members, facilitating collaboration and shared decision-making that can inform the directions of future interventions. Communication asset mapping is a structured approach to identify and evaluate community resources and capabilities to serve as sites for health promotion and education efforts. By identifying assets, community members are empowered to develop strategic approaches to leverage the strengths of their own communities. Both group concept mapping and communication asset mapping can be integrated as steps of the intervention mapping process, which provides a systematic framework for developing and tailoring effective interventions. By integrating these three approaches, community-engaged researchers and their partners can collaboratively design culturally appropriate, feasible, and sustainable interventions tailored to the specific needs and assets of rural communities.